Potencialidades e limites da utilização do GeoGebra em dispositivos móveis em aulas de geometria para os estudantes do 7º ano do Ensino Fundamental - Leandro Augusto Rodrigues Araújo (2023)
This research investigated the potentialities and limits of using the GeoGebra software on mobile devices, in exploratory Geometry activities, based on the responses of 7th grade students to a pedagogical intervention in geometry classes. The activities of this research were designed in such a way as to include the cell phone as a resource that works together with the activities, favoring the production of knowledge, at the same time that it stimulates the participation of the students and allows new perspectives for the mathematics classes. This work presents results from a qualitative research, carried out in the public school in the city of Belo Horizonte, MG, Brazil. We seek to understand how the use of cell phones, along with the GeoGebra software, can enhance students' understanding of the conditions of existence of triangles. Data were collected from participant observation, audio and video recordings, activities answered by students and interviews. The research was carried out based on the study of several authors, with emphasis on João Pedro da Ponte and Marcelo Borba. From the data analysis it was possible to conclude that the GeoGebra software facilitates and speeds up the testing and validation of propositions that students create, but it is necessary for students to have the device and, depending on the school, also have access to the internet on their own. In addition, during data analysis, some situations were highlighted by the students, others perceived by us, and contributed to a more affective and humanized view of the school environment. We developed an educational resource, through a virtual booklet, with the activities of this study, as well as its analyzes and conclusions.